DETERMINATION OF ELECTRIC POWER EXPENSES WHILE OZONIZING AIR CHARGE IN TAKE-IN DIESEL ENGINE COLLECTOR - G. A. Vershina; A. I. Pilatov (Наука и техника)
The paper proposes a method for determination of electric power expenses for an engine. This method makes it possible to determine numerical inter-relation between the pre-determined and required ozone  amount in volume relation with air at cylinder intake and electric power expenses  that are used for dissociation of some oxygen molecules and generation of ozone synthesis processes in the intake flow.The given method can be applied for engine manufacturing  while designing and arranging means for air charge treatment that are used with the purpose to obtain more qualitative impact on an air charge.